Vaccination Attitudes and Experiences of Medical Doctors in Croatia amid the COVID-19 Pandemic: A Social Roles Conflict? - Maja Miskulin; Aida Mujkic; Ivan Miskulin; Zvjezdana Lovric Makaric; Emma Kovacevic; Ljiljana Pintaric; Zeljko Pavic (Vaccines, 2022)
The study aimed to investigate the range of experiences and attitudes of Croatian medical doctors (MDs) related to vaccination and vaccine hesitancy. In January 2021 three asynchronous online focus groups were held using MRQual, a web-based platform, which included 46 MDs from all three levels of the healthcare system in Croatia. NVivo, a qualitative data analysis software package, was used for the thematic analysis of collected data. The participants expressed a high level of support for the Croatian immunization program and vaccines in general. However, some skepticism was expressed regarding new vaccines and the regulatory processes of their approval. A significant number of participants raised concerns over the approval of COVID-19 vaccines, especially given their rapid development. The results also revealed that the process of communication with patients is often based on the very elaborate categorizations of patients based on previous experience, which leads to prioritizing and a communication breakup when dealing with “problematic patients”. MDs find themselves in a delicate situation where a fine balance between time-consuming communication with patients and the demands for maintaining satisfying vaccination uptake is needed. The situation arises from a social roles conflict that is embedded in wider social values and expectations, since communication problems do not arise in the doctor’s office, and therefore cannot be solved without addressing the social forces that cause trust deficiencies. To achieve better immunization results public health leaders need to better understand the social contexts and constraints of MDs vaccine-related behaviors.